EFFECT OF HIGH VOLTAGE ON THE DEVELOPMENT OF THE PLANT TISSUE - Eliška Hutová; Petr Marcoň; Karel Bartušek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
In our experiment the electrical parameters that affect early somatic embryos (ESEs) were investigated. High voltage was generated by a special high voltage generator. High voltages ranging from 5 to 20 kV and frequency of 1 Hz were applied longitudinal and transversal directly on the Petri dish with 2 days old ESEs of Picea abies for periods of 3 hours every day. One Petri dish was placed directly on top of the high voltage generator and on the other Petri dish were fixed two copper plates for transmission of high voltage. Petri dishes were exposed to high voltage for 14 days. After this time, the influence of high voltage was evaluated. To evaluate the experiment were used biological and chemical methods, which confirmed the changes in the growth of ESEs.